Municipal Solid Waste Management 2019
DOI: 10.5772/intechopen.81845
|View full text |Cite
|
Sign up to set email alerts
|

Improper Disposal of Household Hazardous Waste: Landfill/Municipal Wastewater Treatment Plant

Abstract: Household hazardous waste (HHW) is not always separated for proper handling before disposal. When disposed improperly to landfills and municipal treatment plants, these products can have significant impact on the environment. Although HHW is a small portion of municipal solid waste, the presence of HHW in solid management facilities that are not equipped to handle them can have problematic effects, resulting in environmental pollution, damage to facilities, and even injury to workers. In many countries, HHW is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…When inhaled in high doses, several of the solvents used in adhesives and glues have narcotic, potentially deadly effects. Coughing and bronchial spasms might occur after inhaling fumes from cured epoxy resins for several days [15,16].…”
Section: Glues and Adhesivesmentioning
confidence: 99%
“…When inhaled in high doses, several of the solvents used in adhesives and glues have narcotic, potentially deadly effects. Coughing and bronchial spasms might occur after inhaling fumes from cured epoxy resins for several days [15,16].…”
Section: Glues and Adhesivesmentioning
confidence: 99%
“…When consumers are faced with a shortage of facilities for recycling of waste, their level of recycling effort will diminish (Chen and Tung, 2010). Inadequate e-waste disposal facilities will have an impact on solid waste management since households may combine e-waste with general waste that uses different disposal methods (Mahat et.al., 2019;Elbeshbishy and Okoye, 2019). This is because majority of household e-waste has been disposed through different channels before being sent to the recovery facilities, as opposed to the industrial e-waste, which is collected by formal sectors (Osman et al, 2016).…”
Section: Awarenessmentioning
confidence: 99%
“…However, the results aligns with reports found in previous studies that availability of e-waste recycling services and facilities has a direct influence on consumer recycling behaviour (Wong et al, 2019). Nevertheless, past studies highlighted that lack of facilities as the main barriers of respondents' participation in e-waste recycling (Mahat et.al., 2019;Elbeshbishy and Okoye, 2019;Martin et al, 2006).…”
Section: Pearson's Correlation Analysismentioning
confidence: 99%
“…The outcomes indicated that the quality parameters of water exceeded the permissible limits of drinking at many locations leading the water unstable for drinking. Elbeshbishy & Okoye, (2019) have claimed that improper hazardous waste disposal doesn't just contaminate soil and the local water supply, but it can also pollute the air. An area with an ill reputation for a toxic environment can also be susceptible to lower property values, so not following proper disposal procedures can even affect the value of properties.…”
Section: Research Articlementioning
confidence: 99%